1984
DOI: 10.1063/1.94608
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser induced deposition of InP and indium-oxide films

Abstract: InP and In-oxide films have been deposited on quartz, GaAs, and InP substrates by excimer laser induced photodecomposition of (CH3)3InP(CH3)3 and P(CH3)3 vapors at 193 nm. The oxide film refractive index and stoichiometry are close to In2O3. Phosphorus incorporation in the films was greatly enhanced by focusing the laser beam to promote multiple-photon dissociation processes. These conditions also lead to enhanced carbon inclusion in the films, due to formation of species such as CH and CH2 in the gas phase. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The particular material used to construct these lamp envelopes did not permit the emission of the 185 nm radiation line. It has been demonstrated that the Hg-photosensitized decomposition of arsine proceeds as follows (lO) Hg + h~ (254.3 rim) --) Hg* [1] Hg* + AsH3--~ AsH2 + H + Hg [2] AsH2 ~ As + H2 [3] leading to the formation of As films. Here Hg* represents the excited Hg atom and hv represents the photon energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The particular material used to construct these lamp envelopes did not permit the emission of the 185 nm radiation line. It has been demonstrated that the Hg-photosensitized decomposition of arsine proceeds as follows (lO) Hg + h~ (254.3 rim) --) Hg* [1] Hg* + AsH3--~ AsH2 + H + Hg [2] AsH2 ~ As + H2 [3] leading to the formation of As films. Here Hg* represents the excited Hg atom and hv represents the photon energy.…”
Section: Resultsmentioning
confidence: 99%
“…There have been few papers in the past where a low resistivity p-type crystal has been grown. Recently, Yasuda et al (1) succeeded in preparing a p-type crystal and also p-n junction by MOCVD method.…”
Section: Concl Usi Onsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, UV-photochemical vapour deposition (UV-CVD) has been successfully used in the past to deposit numerous metals, insulators, and semiconducting lms. [21][22][23] In photochemical reactions, absorption of light by a reactant molecule enables an inaccessible reaction path to occur by bringing the reactants to the necessary activation energy and also by changing the symmetry of the reactant's electronic conguration. 24 Medium pressure mercury UV lamps are important radiation sources for photochemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various possible TCOs, indium tin oxide ͑ITO͒ is commonly used as a contact for transparent electrodes due to its excellent properties in transmittance, electrical conductivity, substrate adhesion, hardness, and chemical inertness. [1][2][3][4][5][6][7][8] A variety of ITO deposition techniques have been reported, including electron-beam evaporation, 9 dc or radio frequency ͑rf͒ sputtering, 10 reactive ion plating, 11 chemical vapor deposition, 12 and pulsed laser deposition. 13 ITO has been used for interdigitated finger electrodes on metalsemiconductor-metal photodetectors ͑MSM͒, improving the photon responsivity by minimizing blocking of incoming light by the finger electrodes.…”
mentioning
confidence: 99%